저질소 비료 조건에서도 수량성이 높은 중만생 고품질 벼 품종 ‘남찬’ - 박현수; 백만기; 이창민; 서정환; 박송희; 강경민; 박재령; 진민아; 정오영; 정지웅; 김기영 (Korean journal of breeding, 2023)
The rice cultivar ‘Namchan’ was developed to achieve high yields under low-nitrogen fertilizer conditions and enhance cultivationstability. ‘Namchan’ was derived from a cross between ‘Nikomaru’, a Japanese rice cultivar known for its excellent ripening ability inhigh-temperature conditions, and ‘Saenuri’, a Korean mega rice cultivar renowned for its high cultivation stability. To shorten the breedingperiod, anther culture was applied to F1 plants. ‘Namchan’ was selected through the pedigree method, yield trials, and local adaptability tests,with high selection pressure for ripening ability and cultivation stability. The heading date of ‘Namchan’ was August 16, four days laterthan that of ‘Nampyeong’. ‘Namchan’ exhibited strong tolerance to lodging and preharvest sprouting, indicating high cultivation stability. Despitehaving more grains and panicles compared to that in ‘Nampyeong’, ‘Namchan’ exhibited excellent ripening ability, presumed to be inheritedfrom ‘Nikomaru’. ‘Namchan’ showed intermediate resistance to rice blast and resistance to bacterial blight and rice stripe virus. ‘Namchan’had excellent grain appearance, improved milling performance, and superior taste compared to ‘Nampyeong’. ‘Namchan’ exhibited a yieldof 6.34 MT/ha under normal nitrogen fertilizer conditions, and its index at 115%, when compared to that of ‘Nampyeong’, is the highestamong Korean japonica rice varieties. It exhibited a high yield of 5.45 MT/ha even under low-nitrogen fertilizer conditions. ‘Namchan’ ispromising as an outstanding cultivar that can contribute to carbon neutrality through the reduction of nitrogen fertilizers and greenhouse gases(Registration No. 8134) KCI Citation Count: 0